FROM THE PULPIT TO THE ALGORITHM: MILLENNIAL DIGITAL DA'WAH MANAGEMENT STRATEGY IN THE HIJRAH YOUTH SHIFT ECOSYSTEM AND WRITING PAUSE - Neneng Hasanah; Randi Tamirano; Sandi Maspika; Haikal Romadhan Al Yusad (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
The transformation of the da'wah medium from a conventional pulpit to an algorithmic environment necessitates a new managerial framework. This study aims to analyze the digital da'wah management strategies within the ecosystems of Hijrah Youth Shift and Jeda Nulis. Employing a qualitative approach with a four-stage netnographic design (data entry, observation, interpretation, and validation), this study analyzed 200 top-performing content units across YouTube, Instagram, and TikTok from December 2025 to May 2026. The findings reconstruct the classical POAC management functions into the